2021
DOI: 10.18632/aging.203356
|View full text |Cite
|
Sign up to set email alerts
|

CC16-TNF-α negative feedback loop formed between Clara cells and normal airway epithelial cells protects against diesel exhaust particles exposure-induced inflammation

Abstract: CC16 is almost exclusively expressed in non-ciliated epithelial Clara cells, and widely used as a Clara cell marker. Diesel exhaust particles (DEPs), the fine particulate matters produced by diesel engines, cause or exacerbate airway-related diseases. Our previous study documented that DEP inhibits the CC16 expression in the immortalized mouse Clara cell line through methylation of C/EBPα promoter. However, the molecular mechanism by which DEP regulates CC16 secretion is unclear. Here, we isolated CC16 contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…On one side, TNF induced CCSP secretion in club cells [74]. This effect was also noticed after exposure of club cells to diesel exhaust, as a useful restoration of CCSP secretion after the DEP-generated methylation of C/EBPα promoter of SCGB1A1 [75].…”
Section: Modulation Of the Fibrotic Processmentioning
confidence: 71%
“…On one side, TNF induced CCSP secretion in club cells [74]. This effect was also noticed after exposure of club cells to diesel exhaust, as a useful restoration of CCSP secretion after the DEP-generated methylation of C/EBPα promoter of SCGB1A1 [75].…”
Section: Modulation Of the Fibrotic Processmentioning
confidence: 71%
“…The current study showed that CC16 could reduce the release of non‐type 2 inflammatory cytokines (IL‐8 and MMP‐9) from AECs in response to HDM. Previous studies reported that CC16 could reduce tumour necrosis factor [TNF]‐α, IL‐1β, IL‐8 and MMP‐9 in response to LPS and diesel exhaust particles through inhibiting the expression of NF‐κB pathway 33–35 . Meanwhile, the overproduction of oxidative stress from AECs upon environmental stimuli/irritant exposure‐induced non‐type 2 inflammation through the production of IL‐8, IL‐1β and TNF‐α 7,36,37 .…”
Section: Discussionmentioning
confidence: 99%
“…Club cell secretory protein (CCSP), also known as club cell protein 16 (CC16) or CC10, is a 15.8 kDa protein primarily released in the terminal bronchioles, where club cells are located (Almuntashiri et al 2020). CC16 plays a signi cant protective role in reducing oxidative stress and in ammation in the respiratory tract, while also serving as a peripheral lung marker to assess the integrity and permeability of lung epithelial cells (Hu et al 2021). More speci cally, CC16 has the potential to be a therapeutic target for COPD (Martinu et al 2023).…”
Section: Introductionmentioning
confidence: 99%